SOSIALISASI PENGGUNAAN PENJEMUR KOPI OTOMATIS DI KANTOR UD. PUTRO TANI SERDANG BEDAGEI - Ahmad Yanie; Sapran Pulungan; Windy Aulia; Agung Prasetyo; Dwika Wijaya; Didik Sinaga; Thamrin Saragih (HIMPUNAN DOSEN GEMILANG INDONESIA, 2021)
Coffee is a type of plantation plant that is cultivated and has a fairly high economic value. Indonesia is one of the most developed coffee producing countries. However, along with the abundance of coffee production in Indonesia is not balanced by sophisticated equipment for the automatic drying process of coffee beans. Where in the process of drying coffee beans are usually done outdoors so that the coffee beans dry quickly. As a result, under certain conditions, the process of drying coffee beans encounters obstacles when the rain suddenly comes. This is what often happens so that it decreases the quality of coffee beans and causes losses for coffee farmers in Indonesia. Where is the tool that will be needed an Automation program for Coffee Bean Drying Tools that uses an Arduino uno microcontroller. The program in this system uses rain sensor inputs and light sensors as a roof drive to open and close automatically by utilizing sunlight and rainwater. Arduino itself is used as a data processor. While the output on this tool is in the form of a 16x2 LCD Display which functions to display data from arduino which is used as a timer for the predetermined coffee bean drying process. With this tool, it is hoped that farmers will feel calmer when the coffee bean drying process takes place. So there is no need to feel restless or anxious because the drying of coffee beans will not be exposed to rainwater